Developing Government Bond Markets : A Handbook - World Bank; International Monetory Fund (Washington, DC, 2013)
This handbook is designed as a reference source for two distinct user groups involved in the development of government bonds markets: 1) senior government officials responsible for developing the government bond market; and 2) individuals responsible for guiding the market development process at the operational level, and who have a substantial need to understand the policy issues involved. The handbook is structured as follows: Chapter 1 provides an overview of certain policy considerations relevant to developing a government bond market. This overview considers key issues, but at a level of generality appropriate for senior govenrment offcials responsible for making key strategic decisions. The remaining eleven chapters present more detailed discussions of key policy issues, including substantive considerations relating to implementation. The handbook's primary emphasis, however, focuses on the policy dimension of developing medium-and long-term bond markets. It is not intended as a technical manual for use by individuals engaged in day-to-day implementation or operations. The handbook also provides bibliographic and website references for those interested in pursuing further issues covered. A comprehensive glossary of terms related to securities markets appears at the end of the handbook.